Analisis Kinerja Portofolio Optimal Pada Saham Yang Terdaftar di Jakarta Islamic Index (JII) Pada Masa Pandemi Covid-19 - Qadarin, Maryam; Rafi, Zainur; Md Pazil, Afifah Hanim (At-Tasharruf "Jurnal Kajian Ekonomi dan Bisnis Syariah", 2023)
The decline in IHSG performance during Covid-19 pandemic period increased investors’ concern to invest in portfolios. This article aims to determine which stocks include the optimal portfolio and a large presentation of proportions, expected return rates and investment risks to be obtained in each of these shares and how the portfolio performance is optimized. 16 companies listed in the Jakarta Islamic Index (JII) from 2020 to 2021 and have never delegated for three periods were analyzed with Single Index Model to determine the optimal portfolio and RVOL to measure its performance. The results of the study showed six qualified shares form an optimal portfolio namely Aneka Tambang with a proportion of funds of 27% and a share performance of 0.057164791, Surya Citra Media with a proportion of 24% and a share performance of 0.006916892, Vale Indonesia of 20% and a share performance of 0.010239808, United Tractors of 15% and a share performance of -0.057674556, AKR Corporindo of 12% and a share performance of -0.082656883, and Adaro Energy of 2% and a share performance of -2.627991592. Of the overall stock forming the optimal portfolio has the expected return rate of 0.09408136 or 9.408% and portfolio risk of 0.021037694 or 2.104%